Changes in apparent diffusion coefficients in the normal uterus during different phases of the menstrual cycle - Kido, A; Kataoka, M; Koyama, T; Yamamoto, A; Saga, T; Togashi, K (British journal of radiology, 2010)
This study investigated the apparent diffusion coefficients (ADCs) of the uterine zonal structures (myometrium, endometrium and junctional zone) among reproductive women, and their changes during the menstrual cycle. Magnetic resonance (MR) images of seven healthy females (aged 24-31 years) were obtained during the periovulatory, luteal and menstrual phases. Diffusion-weighted imaging (DWI) was performed with a single-shot echo-planar imaging (EPI) sequence in the midsagittal plane of the uterus using three b-values (b = 0, 500 or 1000 s mm(-2)). The ADC values of the three uterine zonal structures were measured on an ADC map by placing two regions of interest (ROI) on the corresponding zonal structures. The average changes of ADC values (intra-individual ADC value variation) over three menstrual phases were 0.41 x 10(-3) mm(2) s(-1) (range, 0.08-0.91) for myometrium, 0.55 x 10(-3) mm(2) s(-1) (0.35-0.84) for endometrium, and 0.40 x 10(-3) mm(2) s(-1) (0.18-0.59) for the junctional zone. The ADC values for myometrium and endometrium were lower in the menstrual phase, although there was some overlap of individual values. Interindividual variation in ADC value for a given zone or phase ranged from 0.48 x 10(-3) mm(2) s(-1) to 0.85 x 10(-3) mm(2) s(-1). Intermeasurement variation between the two ROIs ranged from 0 to 0.48 x 10(-3) mm(2) s(-1) per measurement. The magnitude of these variations was comparable to reported differences between malignant and non-malignant tissues. These preliminary results, from a small number of subjects, suggest that the menstrual cycle and individual variation in pre-menopausal women should be considered when interpreting the ADC values of uterine structures.